Alterations in energy consumption and plantar pressure distribution during walking in young adults with patellofemoral pain syndrome - Figen Dag; Ugur Dal; Zeynep Altinkaya; Ayhan Taner Erdogan; Emre Ozdemir; Didem Derici Yildirim; Mehmet Colak (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of this study was to determine the alterations of walking energy expenditure and plantar pressure distribution in young adults with patellofemoral pain syndrome (PFPS). Methods: Thirty five individuals (mean age: 21.31 ± 1.76) with PFPS constituted the patient group and forty healthy participants (mean age: 21.40 ± 2.11) the control group. Preferred walking speeds (PWS) were determined on the over ground. Individuals walked on a treadmill for 7 min at their PWS and 30% above PWS and oxygen consumption was recorded via a metabolic analyzer. Net oxygen consumption was calculated for each walking trial. Borg scale was applied to assess perceived exertion during walking trial. Plantar pressure distributions were measured by a pedobarography device. Plantar area was subdivided into six zones to evaluate the dynamic plantar pressure data. Results: The mean PWS of PFPS and control groups were 4.69 ± 0.51 and 4.52 ± 0.60 km/h, respectively (p > .09). No significant difference was observed in energy expenditure during walking at PWS between 2 groups while oxygen consumption during 30% above PWS was higher in patient group (18.72 ± 3.75 and 16.64 ± 3.27) (p = .007). Net oxygen consumption was also found to be higher in PFPS group (15.12 ± 3.62 and 13.04 ± 3.24) (p = .005). The mean Borg scores were significantly higher in PFPS group at each walking trials (p < .001). No statistically significant difference was found between weight distribution (%) of symptomatic and nonsymptomatic extremity (50.45 ± 3.92% and 49.56 ± 3.93%, respectively) (p = .509). Dynamic pedobarography parameters were not different between 2 groups, and also between symptomatic and nonsymptomatic extremities (p > .05). Conclusion: Although, rate of perceived exertion and energy expenditure during walking at 30% above PWS are affected negatively in young adults with PFPS, we may speculate that energy consumption and plantar pressure distribution can be compensated by a physiologic adaptation mechanism during walking at PWS. Level of evidence: Level III, Therapeutic Study. Keywords: Energy consumption, Patellofemoral pain syndrome, Plantar pressure distribution, Young, Walking